Implementasi Media Sosial Tik Tok Dalam Pembelajaran Bahasa Indonesia di SD Muhammadiyah Pahonjean Dengan Perbantuan Aplikasi Canva Dan Capcut - Rena Sulistyaningrum; Siti Uswatun Hasanah (Departement of Mathematics Education, 2024)
The development of the era makes technology change so rapidly along with the development of science and technology including the development of the internet and social media in human life. The internet also makes the communication structure faster in interacting between humans. The number of social media applications makes people tend to watch their social media rather than reading newspapers or watching on television. The current phenomenon is that people are more interested in watching short videos on the Tik-Tok social media application. Judging from the objects and results to be achieved, this study can be classified as descriptive research using qualitative methods. Qualitative research methods are a way or method of research that emphasizes analysis or descriptiveness. TikTok, in addition to helping with writing competencies, can also help with listening, speaking and listening competencies, for example, in speaking competencies with TikTok, students can upload videos of poetry readings or lectures. Students will feel proud when the video is liked and gets a lot of comments. Students are very interested if they work in groups and make animations or short videos then they upload or the teacher uploads them on TikTok. The assessment will also be fun because they will compete to get the most likes from viewers or viewers. TikTok, in addition to having a short video display, also has a comment column and a like button. The column and like button can be used as a project assessment tool for students. Students will thus compete to create the best project and share their video links on various social media statuses in order to get the most likes and the best grades.